Pelaksanaan Perlindungan Ekonomis Bagi Pekerja Migran Indonesia : (Studi Di Kota Mataram) - Gusti Ayu Rani Yolanda Devi; H. Zaeni Asyhadie (Fakultas Hukum Universitas Mataram, 2022)
This research purposes are to know the implementation of economical protection for Indonesian migrant worker in Mataram, which discuss how its implementation and what is inhibiting factors in implementation. Method of this study is empirical legal research. Based on research’s result, it can be known that economical protections are in the form of providing social security, wages protection and also socialization on the wages. The provision of social security and also the socialization carried out for Indonesian Migrant Workers from an economic, social and technical perspective has been carried out well. The factors that hinder the implementation of economic protection for Indonesian Migrant Workers are the lack of information from the relevant apparatus, the illegal status of Indonesian Migrant Workers, and the lack of knowledge of Indonesian Migrant Workers in managing the wages earned during their work.